2002
DOI: 10.14310/horm.2002.1166
|View full text |Cite
|
Sign up to set email alerts
|

β-thalassemia and gonadal axis: a cross-sectional, clinical study in a Greek population

Abstract: beta-thalassemia (beta-thal) is characterized by disturbances of the reproductive system. The aim of the present study was: 1) to assess the hypothalamic- pituitary-gonadal axis in patients with beta-thal in relation to their phenotype and 2) to determine prognostic features of current gonadal status. We studied 135 patients (67 males and 68 females) with beta-thal through history, physical examination, spermiograms and GnRH test. These patients were divided into beta-thal major (51 males and 62 females) and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Delayed puberty and hypogonadism are the most common endocrine common complications in β -TI and are attributed to iron-mediated damage leading to dysregulation of the hypothalamic-pituitary axis [ 9 , 25 , 26 , 28 30 ]. Delayed puberty is defined as no puberty in girls by 13 years and in boys by 14 years.…”
Section: Endocrine Complications In β -Timentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed puberty and hypogonadism are the most common endocrine common complications in β -TI and are attributed to iron-mediated damage leading to dysregulation of the hypothalamic-pituitary axis [ 9 , 25 , 26 , 28 30 ]. Delayed puberty is defined as no puberty in girls by 13 years and in boys by 14 years.…”
Section: Endocrine Complications In β -Timentioning
confidence: 99%
“…Hypogonadism is defined as absence of testicular development in boys and breast development in girls by 16 years. Hypogonadic hypogonadism is the most frequent and often undertreated endocrine complication of β -TI, seen in 24% of patients, affecting females more than males [ 9 , 25 , 30 ]. It has been shown to be correlated with early onset of transfusion therapy and serum ferritin levels of approximately 2000 ng/mL in TM patients [ 31 ] and high LIC [ 21 ], increasing age [ 25 ] and HU treatment [ 9 ] in β -TI patients.…”
Section: Endocrine Complications In β -Timentioning
confidence: 99%
“…Reproductive capacity in TM women cannot be well predicted by means of age, menstrual status, or transfusion and chelation parameters. 1,9 Yet, as overall survival continues to improve, 10,11 attainment of reproductive capacity is crucial for many patients, a concern often brought up to the hematologist.…”
Section: Introductionmentioning
confidence: 99%
“…Gradual increase of iron deposition in different organs could be responsible for tissue damage and a number of complications including impaired growth and puberty delay in these patients. [2][3][4][5] Pubertal development and fertility are determined proved the protocol of this study, which is in accordance with the internationally accepted principles as found in the European Community guidelines (EEC Directive of 1986; 86/609/EEC) and the US guidelines (NIH publication #85-23, revised in 1985). Ninetyeight homozygote beta-thalassemic patients, aged 18-23 years attending the special clinic participated in this study.…”
Section: Introductionmentioning
confidence: 99%